Special features for functionalization of carbon nanotubes nanopowders - N. O. Oliinyk; G. D. Ilnytska; G. A. Bazaliy; I. M. Zaitseva; M. A. Marinich; O. M. Sizonenko; A. S. Torpakov (Хімія, фізика та технологія поверхні, 2019)
Physical and mechanical properties of carbon nanotube (CNT) powders depend on the method of their synthesis and chemical refinement. In order to create new composite materials that contain CNT powders as a filler, it is necessary to achieve functionalization of powder surface.